2015
DOI: 10.1007/s40033-015-0074-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Multi Wall Carbon Nanotubes (MWCNT) Reinforced Sintered Magnesium Matrix Composites

Abstract: Metal matrix composites (MMCs) reinforced with ceramic nano particles (less than 100 nm), termed as metal matrix nano composites (MMNCs), can overcome those disadvantages associated with the conventional MMCs. MMCs containing carbon nanotubes are being developed and projected for diverse applications in various fields of engineering like automotive, avionic, electronic and bio-medical sectors. The present investigation deals with the synthesis and characterization of hybrid magnesium matrix reinforced with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…CNT were able to fill the voids in between the Cr 2 O 3 particles due to enhanced melting, which has led to increase in hardness of composite coatings with increase in CNT content. Feng et al [19], Bhaskar et al [29] and Anand and Natarajan [24] have revealed that increase in hardness of CNT reinforced composites is due to suppression of crack formation and enhanced dispersion hardening. The increment in hardness of composite coatings has strongly confirmed the role of CNT reinforcement as reported in the literature [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…CNT were able to fill the voids in between the Cr 2 O 3 particles due to enhanced melting, which has led to increase in hardness of composite coatings with increase in CNT content. Feng et al [19], Bhaskar et al [29] and Anand and Natarajan [24] have revealed that increase in hardness of CNT reinforced composites is due to suppression of crack formation and enhanced dispersion hardening. The increment in hardness of composite coatings has strongly confirmed the role of CNT reinforcement as reported in the literature [30][31][32].…”
Section: Discussionmentioning
confidence: 99%